Agronomic performance and estimated genetic diversity among soybean inbred lines based on quantitative traits - Guilherme S. Medeiros; Pablo D. S. Cabral; Fernando H. L. e Silva; Jôsie C. de O. Freitas; Luís H. R. de Campos; Arthur M. M. F. Carrijo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Although soybean is one of the most important agricultural commodities in the world, it has been losing genetic diversity in recent decades, due to the intense breeding process and reproduction method. Thus, the objective of this study was to evaluate the agronomic performance and estimate the genetic diversity among inbred lines, and identify promising crossings. A total of 66 soybean genotypes were evaluated, 61 of which were pre-commercial lines, and five commercial cultivars (AS3797, DESAFIO, M7110, M7739, M8210) as controls. The experimental design consisted of randomized blocks with three replicates. The distance matrix between the inbred lines was calculated by Mahalanobis distance and grouping by the unweighted pair group method with arithmetic mean (UPGMA). The maximum distance was 1,776.26 between cultivar M7110 and the G23 inbred line, and the minimum 1.50 between inbred lines G13 and G36, with an average distance of 364.40, demonstrating genetic diversity. The traits that contributed most to genetic divergence were number of days to flowering (66.7%) and physiological maturation (28.55%). Inbred lines G60 (higher grain yield), G51 and G33 (lower physiological maturation) and cultivar M7110 (greater divergence) stood out. Four groups were formed, with G1 having the highest grain yield and fewest days to flowering and physiological maturation. The indicated crossings are between G60, G57, CD2728, M7110, G33 and G32 (group G1) and G47 (group G4).